Primary Tokophobia Rooted in Developmental Trauma: A Case Study of Reproductive Fear in Adulthood (London Journal of Medical and Health Research, 2025)
This case study explores a rare presentation of tokophobia—an intense, pathological fear of childbirthin a 38-year-old Togolese woman named Afi, situated within a highly pro-natalist cultural context. Unlike the normative expectations in Togo, where motherhood is celebrated and socially reinforced from an early age, Yawadeveloped a persistent fear of pregnancy and childbirth following early developmental trauma and using an integrative therapeutic approach—including cognitive-behavioral therapy, imagery desensitization, psychoeducation, and observational exposurethe intervention aimed to reframe traumatic associations and restore autonomy in reproductive decision-making. The treatment was framed within a solution-focused and brief therapy model and culturally adapted to fit collective values. The findings underscore the importance of trauma-informed, culturally sensitive interventions in underrecognized mental health conditions such as tokophobia, particularly in African contexts where such cases are seldom documented. While the results are not generalizable, this case contributes to the emerging literature on reproductive trauma in non-Western settings.
Keywords: Quality improvement; brazil; organ transplantation; management program; PAT-MA; health systems; Maranh; pulmonary hypertension.; Chronic thromboembolic pulmonary hypertension; Thrombendarterectomy; Pulmonary vascular resistance; Long-term medical history.; HIV; cervical cancer; Screening; CIN; HPV; Togo.; Tokophobia; Developmental trauma; Cognitive-behavioral therapy; Reproductive mental health; Cultural psychiatry